Public Debate on NCERT History Textbooks: Analysing Tweets on Mughals - Shukla Ojha, Seema (Indian Journal of Educational Technology, 2024)
In April 2023, NCERT brought out rationalised textbooks, which generated heated debate on social media. The present study examined this recent public debate on Twitter (now X) over the supposed removal of Mughal history from NCERT history textbooks by analysing tweets for nearly a month. The study sought to find out how X was used to share information and opinions. The findings show that X posts have both a direct and immediate effect on the perception of public opinion and that a better understanding of how different viewpoints shape the debate on X is highly important. The findings also bring forth a possibility to identify potentially misleading information on the platform. How all this puts greater responsibility on organisations like NCERT in bringing textual material or in anticipating responses to changes/modifications made in its textbooks or its future textbooks and in responding to them effectively are other aspects highlighted in the paper.